Manfaat Penggunaan Lentera terhadap Tingkat Pengetahuan Mahasiswa Jurusan Jurnalistik UIN Alauddin Makassar - Jafar, Iftitah; Nur Amrullah, Mudzhira; Yunas, Andriani; Gufran (Jurnal Publisitas, 2023)
The aim of this study is 1. to determine the level of effectiveness of using Lentera on the level of understanding of students of the Department of Journalism, Alauddin State Islamic University, Makassar, and 2. to determine the inhibiting factors of students when using Lentera in their process of learning. This type of research is quantitative, with a scale of effectiveness of media use and level of understanding. All members of the population were used as a sample in the study, which was 84 college students. Data collection techniques through questionnaires that are disseminated to respondents through Google Forms and documentation. The data processing techniques used are editing, coding, and tabulation. For analytical techniques, correlation analysis is used, classical assumption tests (normality tests, linearity tests), simple linear regression analysis, hypothesis tests (t-tests), and conclusions are drawn. The results showed that the effectiveness of using Lentera on the level of understanding of students of the Department of Journalism was low. As for the level of effectiveness, r square = 0.133 or 13.3%. The value is in the category of 0.00 – 0.199 which means it is in the very low category. The remaining 86.7% were influenced by other factors not measured in the study. Based on the hypothesis test using the t-test, t-count = 3.545 > t-table = 1.663 at a significance level of 5% so that Ha is accepted and H0 is rejected. Some things that become obstacles for students in learning with Lentera include, the information presented is not easy to understand so it affects the mastery of the material, enthusiasm in completing tasks caused by lack of motivation given, and time efficiency in using Lentera. The researcher suggested that another study on this issue should be conducted especially for the lecturers of the Faculty of Da‘wa and Communication is the use of Lentera as a medium of teaching.